Fiber properties of kenaf (hibiscus cannabinus l.) grown between rubber trees / Suhaimi Muhammed ... [et al.] - Muhammed, Suhaimi; Shafie, Amran; Suratman, Mohd. Nazip; Abd. Rashid, Noor Azrieda (2008)
Kenaf plant (Hibiscus cannabinus L.) are becoming popular due the nature of fast growing and having unique properties which can be used as an alternative source for the manufacture of fiber-based products. Young kenaf plants aged between three to four months planted in the rubber plantation (clone RRIM 2024) were studied for the fiber properties such as fiber length, fiber diameter, cell wall thickness and lumen width. Variation of fiber properties was assessed for three different height levels namely top portion, middle portion and bottom portion (basal). Fiber length of kenaf tree showed significant variation for the three height levels with the longest fiber at the bottom portion of the tree (1.97 mm). Similar trend was exhibited by fiber diameter (86.9 µm). The vertical variation of cell wall thickness and lumen width followed the same trend with the thickest fiber wall (20.3 µm) and the largest lumen width (46.4 µm). Such findings revealed that fiber source from the bottom portion of kenaf plants has great potential in the hope to fulfill the need for alternative source of fibers much needed in the manufacture of composite materials including fiber-based products.